(untitled) (Eternitas: Jurnal Teknik Sipil, 2023)
The rapid development of technology is directly proportional to the request of the project owner to complete the work in a fairly short time. This study aims to find the dimensions and amount of reinforcement, as well as the quality of concrete that meets. The dimensions of the tank in this study have a diameter of 17.66 m and a height of 10.965 m with a planned capacity of 2,500 m3. While the planned pile cap dimensions are 19.47 m in diameter with a planned thickness of 40 cm. The planning standard used is API 650 of 2019 published by the American Petrolium Institute. Meanwhile, the repetition that is not in API 650 is determined based on SNI 1727:2020 and pile cap repetition using SNI 2847:2019. The software used is STAAD Pro Connect Edtion v.22. As for the calculation of strouss foundation repetition using PCA COLUMN v6.0. From the planning calculations, it can be determined that the double repetition for the pile cap is D16-150 (thread reinforcement diameter 16 mm, distance 150 mm) with (f’c) = 29.05 Mpa (concrete K-350), (fy) = 320 Mpa, and concrete blanket thickness 70 mm. Meanwhile, for the strouss foundation, 18D16 main reinforcement is evenly distributed on all sides of the circle with a minimum distance of 65 mm and a minimum concrete blanket thickness of 60 mm.